2008
DOI: 10.1002/elan.200804214
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescence of Tris(2,2′‐bipyridine)ruthenium with Various Co‐reactants under Ultrasound Irradiation

Abstract: Electrochemiluminescence (ECL) of tris(2,2'-bipyridine)ruthenium, Ru(bpy)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…10,11 The ECL intensity was strongly dependent on the pH of the solution, and the signal could not be observed at acidic or neutral condition at previous report. 10 In MeCN, oxidation of H2A and Ru(bpy)3 2+ was observed around +1.0 and +1.2 V, respectively (the solid line in Fig.…”
Section: +mentioning
confidence: 66%
See 4 more Smart Citations
“…10,11 The ECL intensity was strongly dependent on the pH of the solution, and the signal could not be observed at acidic or neutral condition at previous report. 10 In MeCN, oxidation of H2A and Ru(bpy)3 2+ was observed around +1.0 and +1.2 V, respectively (the solid line in Fig.…”
Section: +mentioning
confidence: 66%
“…It suggested that ECL quenched by H2A as was proposed in our previous studies. 10,11 The generated *Ru(bpy)3 2+ at the electrode surface could be quenched by charge transfer between *Ru(bpy)3 2+ and H2A as suggested below, Figure 4(A) presents the electrochemical behavior of 0.50 mM DHA in MeCN. Although DHA is easily hydrolyzed to the corresponding hemiketal in aqueous media, it is very stable in dry MeCN.…”
Section: +mentioning
confidence: 96%
See 3 more Smart Citations